Species Composition and Ecological Features of Freshwater Helminthfauna of Seabirds on the Barents Sea - V. V. Kuklin (Российский паразитологический журнал, 2020)
The purpose of the research is integration and classification of data on the species composition of the helminths with freshwater life cycles in the birds on the Barents Sea and analysis of the infection features of birds of different species, depending on the ecology of parasites and hosts. Materials and methods. The material from 729 samples of seabirds belonging to 17 species collected during the period from 1991 to 2017 in several regions of the Barents Sea (Murman coast, Novaya Zemlya, Spitsbergen, offshore water, Pechora Sea) and in 2 regions of the western part of Kara Sea (eastern part of the Karskie Vorota Strait and Baidaratskaya Bay) was studied. The species composition of helminthes and quantitative parameters of birds infection (prevalence of infection, PI, and abundance index, AI) were determined. The statistical processing of the results using the Fisher F-distribution and cluster analysis by the "nearest neighbor" method using the data on PI was carried out.Results and discussion. 30 species of helminths with freshwater life cycles (10 species of trematodes, 14 species of cestodes, 5 species of nematodes, 1 species of acanthocephalans) were found in birds on the Barents Sea. The greatest number of freshwater parasites is typical for kittiwakes and black-backed gulls (9 species each), purple sandpipers (10 species) and herring gulls (11 species). 5 species of birds (little auks, razorbills, Atlantic puffins, Arctic terns and Steller,s eiders) were not infested by these parasites. The most widespread were nematodes Paracuaria adunca and Streptocara crassicauda, found in 5 and 8 species of hosts, respectively. In birds nesting far from the coast (Heuglin's gull, purple sandpiper, king eider), parasites predominate, in which the role of intermediate hosts is played by freshwater invertebrates. For most species of gulls (herring gull, black-backed gull, kittiwake, glaucous gull), used in the breeding season as forage biotopes sea and fresh water, more characteristic of the presence of helminths in the circulation of which fish are involved. In birds that do not have trophic connections with freshwater biocoenoses in the breeding period (alcids, northern fulmar, common eider), parasites are most often found showing wide specificity to different types of hosts and a high tolerance to fluctuations in salinity and temperature. Infestation of this group birds by freshwater helminths occurs either with a prolonged stay in the desalinated areas of the marine aquatory, or with consumption of migratory fishes after their release into the sea.